Analisa Kerusakan Thrust Bearing Turbin Pengaruh Kinerja Pelumas Di Pltu Pt. Pln Np Up Belawan - Mayrini, Irin; Abdilah, Tomi; ., Supriadi (Rekayasa Material, Manufaktur dan Energi, 2025)
The function of lubricants for combustion engine technology and energy conversion machines is very important. It is like a human body without blood will experience death. Steam turbines are a source of electrical energy that can produce large amounts of electrical power. Steam turbines can work well with a number of components needed, including a lubrication system. When the turbine rotates, friction occurs between the bearings and the generator, so to minimize friction and wear, lubricants are needed. Lubricants not only function to prevent wear and tear but also function to transfer heat, remove dirt and cool turbine and generator bearings. A good lubrication system will greatly influence the working reliability of the steam turbine with optimal electrical power production results. On the other hand, if the turbine lubricant system does not work optimally, friction and wear will occur and cause corrosion which will result in damage to the steam turbine thrust bearing components. The research method used is qualitative research, namely data collection through field observations, interviews, lubricant tests in the laboratory and bibliography. The conclusion of this research: the reason the steam turbine lubrication system is not optimal is that the lubricant is contaminated with solid and liquid particles, especially water contamination. This is based on the results of lubricant analysis in the tribology laboratory on November 6 2023 with a lubricant usage period of 11,775 km and water contamination in the lubricant of 4,202 ppm. This figure exceeds the minimum threshold of 200 ppm. Then the next sampling on December 9 2023 with a lubricant usage period of 12,495 Km found water content contamination of 1,064 ppm. And then for the last sampling on July 23 2024 with a lubricant usage period of 16,815 km, water content contamination was still found at 1,165 ppm. After further inspection by the maintenance team in the field, it was found that the source of the water contamination problem came from a leak in the steam turbine gland because the seal strip had over-clearance due to its long life time. This causes some of the turbine steam to enter the lubricant in the bearing. This damage will be repaired during the Major Overhaul because the turbine must be dismantled. A temporary solution, a separator is installed continuously to separate oil and water.